The Effect of Physical Activity on Malondialdehyde (MDA) and Glutathione Peroxidase (GPX) Level as Biomarkers of Oxidative Stress in Young Adults (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2025)
Oxidative stress is a condition characterized by an imbalance between the production of free radicals and the body's ability to neutralize them with antioxidants. In young adults, oxidative stress is a significant risk factor for chronic diseases such as diabetes, hypertension, and heart disease. This study aims to analyze the effect of physical activity on oxidative stress biomarkers, specifically malondialdehyde (MDA) and glutathione peroxidase (GPX), in young adults. A cross-sectional study was conducted involving 50 participants aged 20–30 years, categorized into low, moderate, and high physical activity groups. Physical activity levels were assessed using a questionnaire, while MDA and GPX levels were measured through blood sample analysis using the spectrophotometric method. The data were analyzed using correlation and ANOVA tests to evaluate the relationships and differences in biomarker levels among the physical activity groups. The results showed significant differences in oxidative stress biomarkers and antioxidant capacity between physical activity groups (p < 0.05). Higher physical activity levels were associated with lower MDA levels, indicating reduced lipid peroxidation and oxidative stress. These findings support the promotion of regular, moderate-to-vigorous physical activity among young adults as an effective strategy for enhancing antioxidant defense, reducing oxidative stress, and potentially preventing chronic diseases linked to oxidative damage.